The therapeutic efficacy of transcranial magnetic stimulation in managing Alzheimer’s disease: A systemic review and meta-analysis - Wei, Zhenyu; Fu, Jiaqi; Liang, Huazheng; Liu, Mingli; Ye, Xiaofei; Zhong, Ping (Frontiers in Aging Neuroscience, 2022)
Background Repetitive Transcranial Magnetic Stimulation (rTMS) is widely used to treat Alzheimer’s Disease. However, the effect of rTMS is still controversial. The purpose of the present study is to evaluate the effectiveness of rTMS on cognitive performance of AD patients. Methods We systematically searched relevant literatures in four major databases - PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials [Central] before 28th April 2022. Both randomized controlled trials and cross-section studies that compared the therapeutic effect of rTMS with blank control or sham stimuli were included. Results A total of 14 studies involving 513 AD patients were finally included for meta-analysis. It was found that rTMS significantly improved global cognitive function (SMD = 0.24, 95%CI, 0.12 to 0.36, P = 0.0001) and daily living ability (IADL: SMD = 0.64, 95%CI, 0.21to 1.08, P = 0.004) in patients with AD, but did not show improvement in language, memory, executive ability, and mood. In further analyses, rTMS at 10 Hz, on a single target with 20 sessions of treatment was shown to produce a positive effect. In addition, improvement in cognitive functions lasted for at least 6 weeks (SMD = 0.67, 95%CI, 0.05 to 1.30,P = 0.04). Conclusion rTMS can improve the global cognition and daily living ability of AD patients. In addition, attention should be paid to the safety of rTMS in AD patients with seizures. Given the relatively small sample size, our results should be interpreted with caution.